A new role for human immunodeficiency virus (HIV)-1 protease inhibitors: Suppression of apoptosis - Phenix, Barbara N (University of Ottawa (Canada), 2003)
Protease inhibitor (PI)-induced improvements in CD4 T cell counts may be in part independent of PI effects on HIV replication. Since HIV-associated CD4 T cell depletion occurs by apoptosis, we analysed the effect of Pis on apoptosis in peripheral blood lymphocytes (PBLs) from HIV-infected patients and in an uninfected T cell line. The in vivo effects of Pis were monitored in an animal model of stroke and in HIV negative patients taking anti-retroviral therapy (ART) in the context of post-exposure prophylaxis (PEP). Patient PBLs and Jurkat T cells were cultured with Pis. Following stimulation, apoptosis was measured by annexin-V, and loss of mitochondrial membrane permeability (Deltapsim) was assessed in cells and isolated mitochondria using DiOC6(3). The mechanism of inhibition was determined at the level of caspase activity, and of protein and messenger ribonucleic acid (mRNA) synthesis of various pro- or antiapoptotic factors. For in vivo experiments, mice were given Pis by gastric lavage at various time points prior to and following transient forebrain ischaemia. Histological analyses were performed on hippocampal sections. Apoptosis of ex vivo peripheral blood mononuclear cells (PBMCs) of patients taking PEP (AZT, lamivudine, nelfinavir) was assessed prior to, on, and post-therapy in response to a variety of stimuli. Results revealed that Pis reduced spontaneous and anti-Fas induced apoptosis both in CD4 and CD8 T cells from HIV patients. Jurkat T cell apoptosis, Deltapsi m, cytochrome c release, and caspase 8 cleavage were also inhibited by Pis. The mechanism responsible for inhibition of apoptosis does not involve modification of caspase activity, protein, or mRNA synthesis. Mitochondrial involvement was confirmed following inhibition of viral protein R (Vpr)- and atractyloside (Atr)-induced Deltapsim of isolated mitochondria. Apoptosis in hippocampal sections of mice having undergone transient forebrain ischaemia was inhibited by PI treatment, as was camptothecin-induced apoptosis in PBMCs from patients taking PEP. In conclusion, Pis inhibit apoptosis in PBLs from HIV-infected patients and in uninfected Jurkat T cells. The mechanism appears to involve mitochondria, as inhibition of Vpr- and Atr-induced Deltapsim of isolated mitochondria was observed. Stroke-induced apoptosis may be inhibited in vivo by Pis, and importantly, survival following anti-Fas challenge may be positively influenced.
Keywords: Biology, Molecular.; Biology, Cell.; Health Sciences, Immunology.